Factors associated with citations of articles on circular economy in the Web of Science: modeling for main publishers - Minchón-Medina, Carlos Alberto; Timaná-Palacios, Daphne Jannet; Alvarez-Risco, Aldo; Del-Aguila-Arcentales, Shyla; Yáñez, Jaime A. (Frontiers in Artificial Intelligence, 2023)
The publication of articles on circular economy has different factors associated to explain the citations registered in Web of Science. Articles from the publishers Elsevier, MDPI, Taylor and Francis, Wiley and Springer Nature were evaluated. It is expected that the older the article is, the more citations it receives, but this is not always the case. It has also been recognized that there is a lower number of citations if the articles are too large or if they have too many references. This analysis helps to establish the factors that must be addressed in order to publish in journals that have a high citation rate; likewise, based on specific articles and with specific references, it will be possible to increase the probability of citations.